ChemInform Abstract: Investigation of Electronic and Magnetic Properties of Antiferromagnetic GdSb System by First Principle and Series Expansions Calculations. Issue 17 (28th April 2014) - Masrour, R.; Hlil, E. K.; Hamedoun, M.; Benyoussef, A.
Abstract Review: 25 refs.